The Role of Renewable Energy Sources in Green Planning of Cities and Communities. - Caputo, Paola (Springer, 2020)
Recent estimates suggest that cities account for about 70% of the global energy demand and thereby can be identified as key players to decarbonise the energy generation sector. Among the possibilities to face this challenge, the integration of renewable energy sources into the energy supply mix has a prominent role. Currently, many cities have drastically reduced their energy demand in all final uses and are even boosting a process of 100% energy transition to renewable energy sources. This goal is clearly ambitious not only from an economic point of view, but also even from the technical standpoint, meaning that this integration of renewables is not straightforward. Hence, an effort from academic researchers in order to develop proper methods and tools to support energy planning at urban scale as well as efforts from public services administrations to acquire a proactive role is desired. In this chapter, in order to provide insights into heterogeneous expertise involved in the sector, a framework on the renewables integration at city scale is outlined, highlighting the current main issues and challenges that are encountered, describing some selected experiences and investigating the possible technological solutions.
Keywords: Erneuerbare Energie; Energieplanung; Gebäude; Stadtquartier; Urbaner Raum; Energiesystem; Energiemix; Dekarbonisierung